Clostridium septicum Empyema in an Immunocompetent Woman - Alexander B. Granok; Patrick A. Mahon; Genesio W. Biesek (Case Reports in Medicine)
We report a case of a Clostridium septicum empyema in an immunocompetent woman following operation for an incarcerated internal hernia. The patient was successfully treated with pleural decortication and an extended course of postoperative antibiotics. This is the first report of such an infection in the medical literature.